Prediction of thermal fatigue life based on the microstructure of thermal barrier coating applied to single-crystal CMSX-4 considering stress ratio. Issue 15 (1st August 2021) - Kim, D.H.; Kim, K.K.; Park, K.B.; Yun, J.H.; Seok, C.S.
Abstract: Owing to the repeated operation and shutdown of gas turbines, the thermal barrier coating (TBC) used in these systems undergo thermal fatigue. In such environments, the TBCs fail due to the thermal stress generated at the thermally grown oxide (TGO) interface. As the failure of TBC poses a significant risk to such power generation systems, research combining the thermal fatigue test and the finite element method (FEM) for predicting the failure life of TBCs is being conducted actively. However, previous studies have neglected the compressive stress generated during the cooling stage in the thermal fatigue test. Moreover, variations in the fatigue life depending on the microstructure of the top coating also need to be considered. To this end, this paper proposes a method for predicting the fatigue life of TBCs with various microstructures by using the Goodman method. The influence of the microstructure of the top coating on thermal stress was evaluated using the FEM. The derived tensile stress and compressive stress were converted into a stress amplitude under a stress ratio of −1 by using the Goodman method. A coin-type TBC test specimen was prepared and subjected to a thermal fatigue test, in order to evaluate the durability of the specimen. A master diagram considering the microstructure and thermal shock of the top coating was obtained by applying the converted stress relationship to the results of the thermal fatigue test, and a fatigue life prediction equation was derived. Lastly, the validity of this prediction equation was verified by performing a thermal fatigue test on specimens featuring top coatings with different microstructures.